2017
DOI: 10.1007/s00702-017-1773-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide significant, replicated and functional risk variants for Alzheimer’s disease

Abstract: Genome-wide association studies (GWASs) have reported numerous associations between risk variants and Alzheimer’s disease (AD). However, these associations do not necessarily indicate a causal relationship. If the risk variants can be demonstrated to be biologically functional, the possibility of a causal relationship would be increased. In this article, we reviewed all of the published GWASs to extract the genome-wide significant (p<5×10−8) and replicated associations between risk variants and AD or AD-biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Indeed, APOE has been found to be associated with the atrophies of the hippocampus and amygdala [32]. NECTIN2 , APOC1 , and TOMM40 are neighbor genes of APOE on chromosome 19 [46,47]. In biology, these loci were involved in the deposition of β-amyloid protein and the abnormal phosphorylation of Tau protein [48].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, APOE has been found to be associated with the atrophies of the hippocampus and amygdala [32]. NECTIN2 , APOC1 , and TOMM40 are neighbor genes of APOE on chromosome 19 [46,47]. In biology, these loci were involved in the deposition of β-amyloid protein and the abnormal phosphorylation of Tau protein [48].…”
Section: Discussionmentioning
confidence: 99%
“…2010;Gao, Tian, Gao, & Xu, 2013;Lu et al, 2015;Qiu et al, 2016;Zhai et al, 2016;Michalski, Hofmann, Pitsch, Grosche, & Hartig, 2017;Nguyen et al, 2018;Pimentel-Coelho, Michaud, & Rivest, 2013). However, those studies were designed as overt cerebrovascular insults applied to transgenic mice harboring genetic variants that represent, at most, 10% of the total AD cases [or 20% in the early onset form of Alzheimer's disease; Bekris, Yu, Bird, & Tsuang, 2010;Guo et al, 2017;Kim, 2018)]. Considering the numerous genetic risk factors for AD discovered in genome-wide association studies (Carmona, Hardy, & Guerreiro, 2018;Lambert et al, 2013) In rats subjected to endothelin-induced acute vasoconstriction in the striatum together with intra-cerebrovascular injection of the Aβ fragment 25-35 (Amtul et al, 2014), neurodegeneration markers were found at levels higher than caused by either insult alone (Amtul, Frias, Randhawa, Hill, & Arany, 2019;Amtul, Hill, Arany, & Cechetto, 2018;Amtul et al, 2014Amtul et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Risk variants APOE (rs2075650) and RNU6-560P (rs10792835 + rs3851179) have been linked with AD through genome-wide association studies (GWAS). These risk variants were significantly correlated with nine (6 APOE and 3 RNU6-560P) different piRNAs, showing regulatory capabilities (Guo X. et al, 2017). PiRNA dysregulation may be integral to the development of AD through aberrant downstream signaling.…”
Section: Piwi-interacting Rnamentioning
confidence: 99%